Effectiveness of gastrodin for migraine: A meta-analysis - Zhou, Xiu; Shao, Jingyi; Xie, Xiuzhen; Xu, Yingqi; Shao, Tianyu; Jin, Zhuqing (Frontiers in Neurology, 2022)
Background: Gastrodia elata Blume(GEB), a traditional Chinese medicine, has been widely used in dizziness, numbness of limbs and infantile convulsion, etc. Gastrodin is the main component of GEB. This meta-analysis aimed to evaluate the efficacy and safety of gastrodin in the treatment of migraine; Methods: Ten electronic databases including the Cochrane Library, Embase, EBSCO, PubMed, Web of Science, CENTRAL, CNKI (China National Knowledge Infrastructure), CBM (Chinese Biomedicine Database), WanFang, and VIP (Chinese Scientific Journals Database) were searched for randomized controlled trials (RCTs) of gastrodin for migraine published before September 2021. The data were analyzed by RevMan 5.3 software and evaluated by GRADEpro; Results: A total of 1332 subjects were included in 16 RCTs. The meta-analysis showed that gastrodin was significantly effective in treating migraine (RR = 1.21, 95%CI = [1.17, 1.27]), reducing the pain degree (MD = -1.65, 95% CI = [-2.28, -1.02]), reducing the frequency of migraine attack (SMD = -2.77, 95% CI = [-3.92, -1.62]), shortening the duration of migraine attack (SMD = -1.64, 95% CI = [-2.35, -0.93]), slowing average arterial cerebral blood flow velocity (SMD = -3.19, 95% CI = [-5.21, -1.17]), and safe; Conclusions: This systematic review revealed gastrodin is effective and safe in the treatment of migrain.